An analysis of Filipino girlswear to determine the presence of sexualizing characteristics - Ho, China Monika M. (College of Home Economics, University of the Philippines Diliman, 2021)
The Philippines is identified as a global hot spot for the sexual exploitation of children (Hallare, 2020). However, there is limited literature available on the sexualization of clothing in view of Filipino culture. Sexualization of clothing occurs when a person is sexually objectified through clothing. It will be beneficial to determine what characteristics in girlswear selected Filipinos perceive as sexualizing and the strength of the presence of said sexualizing characteristics in girlswear merchandise. This study proposes to analyze girlswear merchandise, ranging from seven to 12 years old, in a selected local online girls' clothing store to determine the presence of sexualizing characteristics. The results of this study may serve as a reference for Filipino girlswear brands to avoid the sexualization of Filipino girls through clothing. In a research by Bernard and Wollast (2019), it was revealed that sexualized people were perceived as "possessing fewer traits of a human being". This dehumanization of individuals was suggested to be driven by revealing clothing as posture suggestiveness by Bernard et al. (2019) despite clothing itself not being sexual unit until it is worn (Edwards, 2018). This paper proposes a research in two phases. Phase 1 aims to determine what clothing characteristics selected Filpinos perceive as sexualizing, and Phase 2 aims to assess the presence of said sexualizing characteristics among the merchandise sold by selected Filipino girlswear stores. To achieve these objectives, a survey questionnaire and a focus group discussion guide will be utilized for Phase 1, and a document analysis matrix Phase 2. Purposive and convenience sampling will be used for Phase 1 while conveniece sampling will be used for Phase 2. Due to the COVID 19 pandemic, this paper does not present actual data collectinon and analysis. In lieu of actual data collection and analysis, a detailed methodology is proposed.